The triple test as a screening technique for Down syndrome: reliability and relevance - Tim Reynolds (Dove Medical Press, 2010)
Tim ReynoldsClinical Chemistry Department, Queen’s Hospital, Burton-on-Trent, Staffordshire, UKAbstract: The triple test is a second trimester screening test used to identify those pregnant women who should be offered a diagnostic test to identify whether their fetus has an aneuploidy. It was first described in 1988, but has largely been superseded by newer tests either conducted earlier in the first trimester (ie, the combined test, using ultrasound measurement of nuchal translucency,pregnancy-associated plasma protein A, and human chorionic gonadotrophin [hCG]) or in the second trimester (ie, the quadruple test, using α-fetoprotein, hCG, uE3, and inhibin). These newer tests have been introduced because they offer greater detection and lower screen positive results thereby enhancing diagnosis rates, while decreasing the risk of iatrogenic harm caused by the invasive testing required when collecting suitable sample tissue. Noninvasive alternatives to the triple test have been identified, but these have not been adopted despite 13 years of development. It is likely, therefore, that the triple test (or variants thereof) will continue to be used in routine antenatal care for the foreseeable future.Keywords: pregnancy, screening test, antenatal, Down syndrome